Perilaku Organisasi: Keseimbangan Kerja dan Kehidupan terhadap Kepuasan Kerja dalam Mediasi Stres Kerja pada Mahasiswa LLDIKTI IV Universitas Jawa Barat - Afifah, Hana Afifah; Pratiwi, Agustin Riyan Pratiwi (Jurnal Bisnis dan Kewirausahaan, 2025)
The emphasis of the research is on the difficulties faculty members and administrative staff at colleges run under the direction of LLDIKTI IV West Java in reaching work-life balance, as well as the effect of work-related stress on job satisfaction. This study uses the work-life balance theory, which stresses harmonizing workplace responsibilities with personal life to reach job satisfaction and individual well-being. This study is distinctive in that it specifically addresses the link between job satisfaction, work-related stress, and work-life balance inside the framework of universities run under the direction of LLDIKTI IV West Java. With 383 respondents, each representative faculty member—especially those overseeing study programs under LLDIKTI IV West Java—is given questionnaires; Partial Least Square (PLS) analysis is then applied in this quantitative study. The results of this study show that workplace stress is influenced by work-life balance, so job satisfaction follows from this effect. Furthermore, although work stress moderates the link between work-life balance and job satisfaction, work-life balance affects job satisfaction itself.